Soil water balance of intercropped maize and cowpea grown in a tropical hydromorphic soil in western Nigeria - Hulugalle, N.R.; Lal, R. (1986)
Water‐use efficiency (WUE) and soil water extraction by four maize (Zea maysL.)/cowpea (Vigna unguiculataWalp.) cropping patterns were studied in a tropical hydromorphic soil over two consecutive growing seasons in 1983 and 1984. The cropping patterns used were: monocropped cowpea (T1), monocropped maize (T2), intercropped maize and cowpea planted in the same row as alternate plants (T3), and intercropped maize and cowpea planted in alternate rows (T4). Evapotranspiration (Et) was calculated from the soil water balance. Soil water extraction was limited to the surface 0.35 m of the profile due to the restriction of roots by a gravel layer at this depth. Upward water flux into the root zone was negligible due to low hydraulic conductivity. All cropping patterns were subjected to drought stress in 1983. Mean runoff and net water flux in the root zone in 1983 and 1984 were 2.4 and 0.04%, respectively, and 1.4 and 0.4%, respectively, of the seasonal rainfall. Intercropping increased seasonal WUE. The WUE (kg grain per mm water per ha) of T1, T2, T3, and T4were 0.5, 2.2, 1.6, and 1.6, respectively, for the droughty conditions in 1983 and were 2.1, 2.1, 4.2, and 3.6, respectively, for the favorable moisture regime in 1984. One of the benefits of intercropping maize and cowpea is, therefore, a higher WUE in relation to monocropping provided soil water is not limiting